2012
DOI: 10.1159/000335047
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Factors in Major and Macular Branch Retinal Vein Occlusion

Abstract: Concentrations of inflammatory factors were measured in 40 patients with macular edema due to major branch retinal vein occlusion (BRVO) or macular BRVO who were treated by pars plana vitrectomy. Vitreous fluid levels of vascular endothelial growth factor (VEGF), soluble intercellular adhesion molecule-1 (sICAM-1), and pigment epithelium-derived factor (PEDF) were determined. Visual acuity and central macular thickness were significantly improved at 6 months in both groups. Vitreous fluid levels of VEGF and sI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…The novel DDS applicator is a well-established applicator system to apply sustained release of DEX-implants into the vitreous cavity. With favorable confidence in intravitreal DEX injections (17,18,19) among treating physicians, the sharper novel DDS needle will increase in use as confirmed by our measurements in this experimental study.…”
Section: Dds Applicatorsupporting
confidence: 64%
“…The novel DDS applicator is a well-established applicator system to apply sustained release of DEX-implants into the vitreous cavity. With favorable confidence in intravitreal DEX injections (17,18,19) among treating physicians, the sharper novel DDS needle will increase in use as confirmed by our measurements in this experimental study.…”
Section: Dds Applicatorsupporting
confidence: 64%
“…We recently reported that intraocular levels of several inflammatory factors were significantly correlated with the severity of ME in BRVO,3 4 suggesting an important role of inflammation in the mechanism of ME. This hypothesis is supported by the Standard Care versus Corticosteroid for Retinal Vein Occlusion (SCORE) study, which demonstrated that intravitreal injection of triamcinolone acetonide improved both visual acuity and ME after 12 months in patients with BRVO 5.…”
Section: Introductionmentioning
confidence: 98%
“…19,20 Many studies have demonstrated elevation of proinflammatory mediators and reduction of antiinflammatory cytokines of the vitreous fluid in RVO patients. 20,25,26 In addition, Yoshimura et al 19 reported the upregulation of cytokine interleukin-6, interleukin-8, and monocyte chemoattractant protein-1, and their contribution to the formation of RVO. Furthermore, many reports disclosed that after antiinflammatory therapy in RVO patients, macular edema, a serious complication of RVO, subsided together with reduced proinflammatory factors in vitreous fluid.…”
Section: Discussionmentioning
confidence: 99%